DAMPAK PROGRAM CORPORATE SOCIAL RESPONSIBILITY BIDANG KESEHATAN PT. PASANGKAYU TERHADAP MASYARAKAT KELURAHAN MARTAJAYA KECAMATAN PASANGKAYU KABUPATEN PASANGKAYU - Andrian; Muzdalifah; Ratu Amanda Busman; Muhamad Riski Nugraha; Riska Ayu Fahrany; Lely Elviana; Anil Zikri; Febrianty; Audietya Chantieka Aura; Friscia Novianti Setiawan; Rachamat; Muzakir Tawil; Askar Mayusa (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Corporate Social Responsibility (CSR) is a form of corporate social responsibility that contributes to improving community welfare, particularly in the health sector. This study aims to analyze the implementation and impact of PT. Pasangkayu’s CSR health program on the community of Martajaya Village, Pasangkayu District, Pasangkayu Regency. The study employed a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation. The findings show that the CSR program was implemented through mobile health services, distribution of insecticide-treated mosquito nets, supplementary feeding for stunted children, health education, fogging activities, and training for Posyandu cadres. The program positively improved access to healthcare services, reduced malaria cases, increased public health knowledge, and encouraged healthier lifestyles. However, challenges remain, including unequal distribution of benefits and limited access to healthcare services.